1995
DOI: 10.1007/bf00688326
|View full text |Cite
|
Sign up to set email alerts
|

5-fluorouracil metabolism and cytotoxicity after pre-treatment with methotrexate or thymidine in human hypopharynx and colon carcinoma xenografts: a19F-nuclear magnetic resonance spectroscopy study in vivo

Abstract: The metabolism of 5-fluorouracil (5-FU) was monitored non-invasively in two xenografts, a hypopharynx carcinoma and a colon carcinoma (CSM) by 19F-magnetic resonance spectroscopy following an i.v. bolus injection of 130 mg kg-1 5-FU. Both the level of fluoronucleotides (FNuc) and the tumor growth delay were significantly higher in the CSM colon carcinoma than in the hypopharynx carcinoma (both parameters, P < 0.001). Administration of 100 mg kg-1 methotrexate (MTX) at 15 h before treatment with 5-FU caused a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Our 19 F MRS results show that the more sensitive C26-10 tumour exhibits a significantly higher conversion of 5-FU to fluoronucleotides (cytotoxic anabolites) compared to the insensitive, more rapidly growing C26-B tumour (C max and AUC in Table 1). These results support previous findings that positive therapy response correlates with the concentration of anabolites achieved in tumour tissue, either directly or with the aid of modulators (McSheehy et al, 1989(McSheehy et al, , 1992Koutcher et al, 1991;Sijens and Ng, 1992;Findlay et al, 1993;Tausch-Treml et al, 1996;Holland et al, 1997). The broad anabolite peak observed in Figure 1 represents the complete family of fluoronucleotides (mono-, di-, triphosphates; oxy-and deoxy forms) which cannot be further distinguished with in vivo 19 F MRS.…”
Section: Discussionsupporting
confidence: 89%
“…Our 19 F MRS results show that the more sensitive C26-10 tumour exhibits a significantly higher conversion of 5-FU to fluoronucleotides (cytotoxic anabolites) compared to the insensitive, more rapidly growing C26-B tumour (C max and AUC in Table 1). These results support previous findings that positive therapy response correlates with the concentration of anabolites achieved in tumour tissue, either directly or with the aid of modulators (McSheehy et al, 1989(McSheehy et al, , 1992Koutcher et al, 1991;Sijens and Ng, 1992;Findlay et al, 1993;Tausch-Treml et al, 1996;Holland et al, 1997). The broad anabolite peak observed in Figure 1 represents the complete family of fluoronucleotides (mono-, di-, triphosphates; oxy-and deoxy forms) which cannot be further distinguished with in vivo 19 F MRS.…”
Section: Discussionsupporting
confidence: 89%
“…Although at the low FU dose no anabolites were detected in normal liver tissue, after injection of low-dose 5FU combined with thymidine anabolite resonances were observed in the liver. TauschTreml et al [94] observed enhanced conversion of FU to fluoronucleotides as well as an increased half-life of FU in both human hypopharynx carcinoma and colon carcinoma xenografts when co-treated with thymidine (400 mg/kg) was performed. The plateau level of fluoronucleotides 50-60 min after injection of a FU bolus (130 mg/kg) divided by the initial concentration was 0.18 ± 0.086 for the hypopharynx carcinoma with thymidine co-treatment, 0.13 ± 0.068 for the corresponding controls and 0.36 ± 0.125 for the colon carcinoma with thymidine co-treatment, 0.24 ± 0.11 for the corresponding controls.…”
Section: Modulation Of Fu Metabolismmentioning
confidence: 97%
“…FdUMP (DNA-directed toxicity) is present at much lower concentrations than FUTP (RNA-directed toxicity) and is expected to make a negligible contribution to the fluoronucleotide resonance. Thus, it was speculated by the authors [94] that in tumors for which DNA-directed toxicity is more important than RNA-directed toxicity, addition of thymidine to FU therapy may lead to an increase in fluoronucleotide levels without affecting tumor cytotoxicity. This seems to be the case for hypopharynx carcinoma and may explain why anabolite formation did not serve as a predictor for the efficacy of the combined treatment with this tumor.…”
Section: Modulation Of Fu Metabolismmentioning
confidence: 97%
See 1 more Smart Citation
“…routes) or modulators to enhance F-Nuctd production generally results in improved therapy response. 61,62,64,[67][68][69][70][72][73][74] The conversion of FU into FUTP and FdUMP via enzyme-catalyzed multistep reactions 31 is an essential prerequisite for cytotoxicity via RNA-or DNA-directed mechanisms. Thus, the amounts of F-Nuctd produced intracellularly can be considered to be a measure of the cytotoxic potential of a given fluoropyrimidine therapy protocol, as shown in animal models 61,68,105 and for ovarian cancer.…”
Section: Treatment Response and Metabolite Profilesmentioning
confidence: 99%